2006
DOI: 10.1159/000095340
|View full text |Cite
|
Sign up to set email alerts
|

Neocortical and Hippocampal Glial Fibrillary Acidic Protein Immunoreactivity Shows Region-Specific Variation during the Mouse Estrous Cycle

Abstract: Ovarian hormones modulate both neuronal and glial activation during the estrous cycle. These effects are particularly well characterized in the hypothalamus. Ovarian hormones also affect brain regions not directly related to reproductive function. In this study we used glial fibrillary acidic protein (GFAP) immunocytochemistry to quantify astroglial cells and process density in both the neocortex and hippocampus during the estrous cycle. Our data show that the density of GFAP immunoreactive processes in the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 106 publications
2
17
0
Order By: Relevance
“…Here, we report an increase in GFAP immunoreactivity, without an increase in the number of cells expressing GFAP. Thus, the apparent increase in GFAP immunoreactivity observed in this study is most likely due to the increase in cell size and number of processes expressing GFAP, corroborating rodent studies (Landfield et al 1977;Lindsey et al 1979;GarciaSegura et al, 1994a, b;Garcia-Segura et al 1994a, b;Berciano et al 1995;Garcia-Segura et al 1996;Struble et al 2006). Moreover, other nonhuman primate studies demonstrate that the cytoarchitecture of glial cells change with age but not the number of glial cells (Peters and Sethares 2002;Sandell and Peters 2002).…”
Section: Discussionsupporting
confidence: 87%
“…Here, we report an increase in GFAP immunoreactivity, without an increase in the number of cells expressing GFAP. Thus, the apparent increase in GFAP immunoreactivity observed in this study is most likely due to the increase in cell size and number of processes expressing GFAP, corroborating rodent studies (Landfield et al 1977;Lindsey et al 1979;GarciaSegura et al, 1994a, b;Garcia-Segura et al 1994a, b;Berciano et al 1995;Garcia-Segura et al 1996;Struble et al 2006). Moreover, other nonhuman primate studies demonstrate that the cytoarchitecture of glial cells change with age but not the number of glial cells (Peters and Sethares 2002;Sandell and Peters 2002).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, it has been observed that GFAP synthesis is accompanied by the growth of glial processes that displace the synaptic terminals (Dhandapani et al, 2003). This estrogenic up-regulation of GFAP expression in hippocampus coincides with two reports showing that GFAP expression in hippocampus peaks on proestrus, implying high levels of E2 (Struble et al, 2006;Arias et al, 2009).…”
Section: Figsupporting
confidence: 86%
“…This protein, among other functions, provides motility and stability to astrocytes, which play a role in synaptic plasticity (Gómora-Arrati et al, 2010). It has been reported that E2 increases the expression of GFAP in hippocampus and several other areas related with reproductive functions (Day et al, 1993;Struble et al, 2006;Garcia-Segura et al, 1994;Kohama et al, 1995). Furthermore, it has been observed that GFAP synthesis is accompanied by the growth of glial processes that displace the synaptic terminals (Dhandapani et al, 2003).…”
Section: Figmentioning
confidence: 99%
“…GFAP process density was calculated by a point count method of grid intersections (Struble, et al, 2006). A 5 X 5 cell grid, 25 μm/cell side, was overlaid on the live image and each immunostained process (but not cell body) intersecting the grid was marked (Fig.…”
Section: Methodsmentioning
confidence: 99%